Diverse Music Listening Modes: Exploring the Historical Interplay between Social Structures, Repertoire, and Cultural Organization of the Senses - Ina Knoth (Musicologica Austriaca)
Historical studies on music listening have experienced significant growth in recent decades. This essay presents a novel approach to investigating historical music listening by reconstructing “music listening modes” from a cultural perspective. It assesses scholarly debates on three of the most intensely discussed aspects of cultural perspectives on music listening to uncover their potential for reconstructing the focuses and properties of attention during music listening: first, audience social structures; second, the range of musical repertoire accessible to these audiences; and third, the cultural organization of the senses. Subsequently, the study explores the impact of aural educational practices on listening modes using primary sources from the Restoration to the mid-eighteenth century. In-depth analyses of two listening accounts exemplify how the balance between sensory organization, available musical repertoire, and social structures was sensitive to changes in any of these aspects. In conclusion, the essay highlights the complex and dynamic nature of music listening practices in the seventeenth and eighteenth centuries, which continue to evolve in response to shifting social and cultural contexts. By illuminating the intricate relationship between sensory organization, musical repertoire, and social structures, this study contributes to a more profound understanding of the historical development of music listening practices.